Verification of Neonatal Tetanus Surveillance Systems in Katsina State, Nigeria - Shafique Sani Nass; Hadi Danawi; Loretta Cain; Monoj Sharma (SAGE Publishing, 2017)
Background: The incidence and mortality rates of neonatal tetanus (NNT) remain underreported in Nigeria. The goal of the study was to compare the NNT prevalence and the mortality rates from the existing surveillance system and active surveillance of health facility records in 7 selected health facilities from 2010 to 2014 in Katsina State, Nigeria. Methods: The study is a retrospective record review using extracted data from NNT records and analyzed using descriptive statistics. Results: The prevalence of NNT and mortality rate were 336 cases and 3.4 deaths per 100 000 population, respectively, whereas the prevalence of NNT and mortality rate reported through the Integrated Disease Surveillance and Response (IDSR) system were 111 cases and 1.0 death per 100 000 population, respectively. Conclusion: The study shows underreporting of NNT in the existing IDSR system. Implications: Active surveillance is a good strategy for verifying underreporting of NNT in the surveillance system. The IDSR system should be strengthened with the capacity to detect events associated with a disease toward global elimination.